Current edge-control strategy for multiple energy routers based on cyber-energy dual modulations - Wang, Rui (2023)
Recently, energy routers have been widely applied in the dc microgrid to achieve the power balance among buses, and the relative control strategies with a communication network assumption have been proposed. However, the communication network assumption cannot be satisfied in a remote mountainous area and an island area. To this end, this article proposes one communication-free edge-control strategy for energy routers based on cyber-energy dual modulation to achieve power balance without the communication network assumption. First, the network structure and the system model are introduced, which is a fundamental pretreatment for the subsequent controller design. Second, the cyber-energy dual modulation approach without additional communication line is designed to exchange the information among distributed generations, which is an indispensable communication environment design for the subsequent controller design. Considering the system model feature and communication environment feature, the periodic dynamic event-triggered edge-control strategy is proposed in this article. Finally, the proposed strategy effectiveness of the energy router is well verified through the dc-dc converter experiment set and the OPAL-RT test system.